Vocabulary related to the sacrament of Eucharist. Fragment of the french-russian thesaurus of religious lexis (part 2) - Nadezda Zhukovskaya (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. 3, Filologii͡a, 2019)
This publication contains a fragment of the French-Russian Thesaurus of Religious Lexis that covers the language of Catholicism and Orthodoxy (and, to a lesser extent, Protestantism)